2018
DOI: 10.3389/fcvm.2018.00132
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dispersion Measures of Conduction and Repolarization in Type 1 Compared to Non-type 1 Brugada Syndrome Patients: An Electrocardiographic Study From a Single Center

Abstract: Background: Brugada syndrome (BrS) is a cardiac ion channelopathy that predisposes affected individuals to sudden cardiac death (SCD). Type 1 BrS is thought to take a more malignant clinical course than non-type 1 BrS. We hypothesized that the degrees of abnormal repolarization and conduction are greater in type 1 subjects and these differences can be detected by electrocardiography (ECG).Methods: Electrocardiographic data from spontaneous type 1 and non-type 1 BrS patients were analyzed. ECG parameters were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
1
7
0
1
Order By: Relevance
“…Firstly, a comprehensive analysis of different ECG features has been performed, with 3–50 ECGs measured per patient, and a total of more than 1000 ECGs analyzed. This extended previous studies using only single ECG measurements at baseline ( Tse et al, 2018b ; Lee et al, 2020 ). Moreover, there is good inter and intra-observer variability, as reflected by the intra-class coefficient.…”
Section: Discussionsupporting
confidence: 74%
“…Firstly, a comprehensive analysis of different ECG features has been performed, with 3–50 ECGs measured per patient, and a total of more than 1000 ECGs analyzed. This extended previous studies using only single ECG measurements at baseline ( Tse et al, 2018b ; Lee et al, 2020 ). Moreover, there is good inter and intra-observer variability, as reflected by the intra-class coefficient.…”
Section: Discussionsupporting
confidence: 74%
“…This study included consecutive patients diagnosed with BrS between 1997 to 2019 identified from searching electronic health records from the Hospital Authority of Hong Kong, as described previously. 12–15 The diagnosis of BrS was confirmed by reviewing the patient case notes and documented ECGs by SL. and GT using the 2017 diagnostic criteria proposed by the Expert Consensus Statement.…”
Section: Methodsmentioning
confidence: 99%
“…Tse et al reported higher QRS dispersion in Type‐1 BrS than non‐Type‐1 BrS. However, no MAE was compared or reported . Our group published a comprehensive systemic review and meta‐analysis on fragmented QRS as a predictor of arrhythmic event in BrS and showed that baseline fragmented QRS increased major arrhythmic events up to 3‐fold .…”
Section: Discussionmentioning
confidence: 90%